A critical review on MXene as promising photovoltaic materials - Kanti P.K.; Jayan K D.; Swapnalin J.; Banerjee P.; Paramasivam P.; Wanatasanappan V.V. (Elsevier B.V., 2025)
This review paper comprehensively examines the diverse applications of MXenes, a class of two-dimensional (2D) materials consisting of transition metal carbides, nitrides, and carbonitrides, in the realm of photovoltaics. MXenes have garnered significant interest due to their exceptional properties, including metallic conductivity, light absorption and transmission capabilities, solubility, and ease of fabrication. The paper focuses on their utilization in various emerging solar cell technologies, particularly perovskite solar cells (PSCs) and organic solar cells (OPVs). Through a thorough examination of recent research, the paper discusses the role of MXenes as additives in photo-active materials, transport layers, and interfacial layers in OPVs and PSCs, highlighting their potential to enhance device performance. It explores MXenes' efficacy as transport materials and versatile electrodes, contributing to the overall efficiency of photovoltaic (PV) device configurations. Furthermore, this review points out that the introduction of bandgap in hybrid material also enhances photovoltaic efficiency. Various experiments and strategies adopted to create the desired bandgap in a metallic MXene-based hybrid structure are discussed. Hence, by shedding light on significant improvements in photovoltaics leveraging 2D materials such as MXene, this review provides valuable insights for researchers and practitioners in the field to work for further advancement. ? 2024